Primary Communication Disorders in the Nashville Schools: 1979-80 - Stewart, James Monroe (Journal of All India Institute of Speech and Hearing)
The study sought to determine the extent of service delivery for communicative disorders in the Nashville public schools during the academic year 1979-80. Of the 71,662 children enrolled in grades K thru 12, 2,877 children or 4.01 percent of the population were receiving services for communicative disorders. Of this number, 2,023 or 2.82 percent were primary and 854 or 1.19 per cent were secondary handicaps. From these figures, it was determined that 70.3 percent of the service delivery was for primary handicaps and the remaining 29.3 per cent for secondary handicaps. The primary handicaps of speech, language, and hearing accounted for 83.2,10.6 and 6.2 per cent respectively. Males (63.5 percent) were seen 1.7 times more often than females (36.5 percent). Quantitatively, there were no apparent racial differences. The in-depth analyses indicated that blacks had a greater propensity for language disorder than whites while whites had a greater propensity for hearing disorders than blacks. The multi- dimensional scaling analysis supported the significance of these and other observations.